A dosimetric evaluation of different levels of energy and intensity modulation for inversely planned multi-field MERT. (3rd May 2018) - Joosten, A; Müller, S; Henzen, D; Volken, W; Frei, D; Aebersold, D M; Manser, P; Fix, M K
Abstract: For inversely planned multi-field modulated electron radiation therapy (MERT), the impact of different levels of energy and intensity modulation on the dosimetric characteristics of MERT plans was investigated. Four cases (breast, skin, larynx, parotid) were selected for this study. One to four different energies and one to four different intensity levels per energy were considered resulting in sixty optimized plans. The optimized plans with the best combinations of one, two, three and four energies considering all intensity levels were selected for final dose calculation. The influence of energy and intensity levels on the homogeneity index (HI) in the planning target volume (PTV) and on organs at risk (OAR) sparing was investigated. Additionally, the difference in the HI between final and optimized plans ΔHI was studied. Energy and intensity modulation both improved the HI in the PTV for the final plans. While intensity modulation had negligible influence on OAR sparing, energy modulation could also improve OAR sparing depending on the selected energies. To achieve a HI > 90% in the PTV, the minimal number of energies required were four for the breast case, three for the parotid and skin cases and one for the larynx case. ΔHI decreased with increasing number of apertures. Overall, energy modulation had a larger impact on the dosimetric characteristics of MERT plans than intensity modulation.